Concentration-dependent mortality of chloroquine in overdose - Watson, JA; Tarning, J; Hoglund, RM; Baud, FJ; Megarbane, B; Clemessy, J-L; White, NJ (eLife Sciences Publications, 2020)
Hydroxychloroquine and chloroquine are used extensively in malaria and rheumatological conditions, and now in COVID-19 prevention and treatment. Although generally safe they are potentially lethal in overdose. In-vitro data suggest that high concentrations and thus high doses are needed for COVID-19 infections, but as yet there is no convincing evidence of clinical efficacy. Bayesian regression models were fitted to survival outcomes and electrocardiograph QRS durations from 302 prospectively studied French patients who had taken intentional chloroquine overdoses, of whom 33 died (11%), and 16 healthy volunteers who took 620 mg base chloroquine single doses. Whole blood concentrations of 13.5 umol/L (95% credible interval 10.1-17.7) were associated with 1% mortality. Prolongation of ventricular depolarisation is concentration-dependent with a QRS duration >150 msec independently highly predictive of mortality in chloroquine self-poisoning. Pharmacokinetic modelling predicts that most high dose regimens trialled in COVID-19 are unlikely to cause serious cardiovascular toxicity.